ENFORCEMENT OF MEDICAL DISCIPLINE VIOLATIONS IN INDONESIA - Wibiansyah, Kukuh Tri; Wahyudi, Firdaus; Bhima, Sigid Kirana Lintang; Dhanardhono, Tuntas (Faculty of Medicine, Diponegoro University, Semarang, Indonesia, 2020)
Background: The medical profession is closely related to human values and professionalism, but in practice, there are still doctors who breach the medical discipline principles. Method: This is a descriptive study to outline the enforcement outcome. Samples were taken from data of breach of medical discipline in 2014-2018 which were uploaded on the website of the Indonesian Medical Council (KKI) combined with interviews reports. Result: The average complaint of breach is 40.6 complaints per year. The percentage of the case completion compare to the number of complaints each year was 82% in 2015, 103% in 2016, 217% in 2017, and 126% by 2018. Total number of decision from medical discipline council trial in 2018 was 49 cases, consists of 4 cases from 2014, 5 cases from 2015, 21 cases from 2016, 16 cases from 2017, and 3 cases of complaints submitted in 2018. Of the verdict from the trial, 15 decision considered as interlocutory verdict and 34 cases as final decision. The period of handling of medical disciplinary breach requires 1 to 2 years. Conclusion: The enforcement of medical discipline violations experienced progressive resolution annually, with 2017 as the peak year. The performance was influenced by alteration in the management board and the enactment of new council regulations.